A feasibility trial of genomics‐based diagnosis detecting insecticide resistance of the diamondback moth. Issue 4 (1st February 2022) - Yamanaka, Takehiko; Kitabayashi, Satoshi; Jouraku, Akiya; Kanamori, Hiroyuki; Kuwazaki, Seigo; Sudo, Masaaki
Abstract: BACKGROUND: Insecticide resistance management has been key for crop protection for over 70 years and is increasingly important because the development of new active ingredients has decreased in recent years. By monitoring the development of resistance in a timely manner, we can effectively prolong insecticide efficacy. Genomic‐based diagnosis can reliably predict resistance development if information on resistant mutations against major pesticides is available. Here, we developed a feasibility trial of genomics‐based diagnosis of insecticide resistance in diamondback moth ( Plutella xylostella ) populations in Nagano Prefecture, Japan. Amplicon sequencing analyses using a next‐generation sequencer (Illumina MiSeq) for major insecticides, including diamides, pyrethroids, Bacillus thuringiensis (Bt) toxin (Cry1Ac), organophosphates, and spinosyns, were conducted. RESULTS: Mutations related to the resistance of pyrethroids, organophosphates, and diamides (flubendiamide and chlorantraniliprole) prevailed, while those of a diamide (cyantraniliprole), Bt (Cry1Ac), and spinosyns were scanty, suggesting that they are still effective. The results of the genomics‐based diagnosis were generally concordant with the results of bioassays. Resistance development tendencies were generally uniform across Nagano. CONCLUSION: An insecticide‐resistance management campaign can be conducted in Nagano Prefecture with a quick genomic‐based diagnosis in early spring while bioassay is the only option for monitoring resistances whose mutations are unavailable. Our study is the first step in the future management of insecticide resistance in all significant pests. © 2022 Society of Chemical Industry. Abstract : Our genomic‐based diagnosis provides fast estimates of resistance development. Only a few male diamondback moths in the early part of the cropping seasons are required to produce prompt results.